KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL TIMSS PADA TOPIK DATA DAN PELUANG - Irma Rizki Amanda; Redo Martila Ruli (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Mathematical problem solving ability is one of the goals of learning mathematics that must be possessed by every student. This study aims to describe the mathematical problem solving ability of junior high school students in solving TIMSS questions on the topic of data and probability. This research uses a qualitative approach with a descriptive method. The research techniques used are tests, interviews, and triangulation. The results of the study were 6 students, 3 students met the indicators of identifying the adequacy of data, 4 students met the indicators of formulating a mathematical problem or making a mathematical model of a problem, 2 students meeting the indicators of applying strategies to solve mathematical problems, 1 student fulfilling the indicators of explaining or interpreting the results accordingly. the initial problem and re-examined the results of the answers, and 2 students fulfilled the indicators using mathematics in a meaningful way. The conclusion in this study is that the mathematical problem solving ability of junior high school students is still relatively low. This is due to several factors, namely students have not been trained to write down important points contained in questions such as what is known and asked, students are accustomed to directly answering questions without using mathematical calculations, in applying solving strategies students still find it difficult, and students are not accustomed to giving conclusions and recheck the results of the answers.